2010
DOI: 10.4049/jimmunol.0904024
|View full text |Cite
|
Sign up to set email alerts
|

F1-Adenosine Triphosphatase Displays Properties Characteristic of an Antigen Presentation Molecule for Vγ9Vδ2 T Cells

Abstract: Material

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 36 publications
(45 reference statements)
1
37
1
Order By: Relevance
“…F1.ATPase-coated beads stably bound to an adenylated derivative of IPP, and promoted TCR aggregation, cytokine secretion, and cytotoxic activity (10). These studies collectively support the concept that activation of Vg9Vd2 T cells requires a certain density of membrane-bound phosphoantigens to induce efficient TCR signaling, which is necessary for the activation of their antitumor cytotoxic properties (4, 5, 7).…”
Section: T-cell Receptor Agonists For Activation Of Vg9vd2 T Cellssupporting
confidence: 58%
See 1 more Smart Citation
“…F1.ATPase-coated beads stably bound to an adenylated derivative of IPP, and promoted TCR aggregation, cytokine secretion, and cytotoxic activity (10). These studies collectively support the concept that activation of Vg9Vd2 T cells requires a certain density of membrane-bound phosphoantigens to induce efficient TCR signaling, which is necessary for the activation of their antitumor cytotoxic properties (4, 5, 7).…”
Section: T-cell Receptor Agonists For Activation Of Vg9vd2 T Cellssupporting
confidence: 58%
“…Although putative interactions between phosphoantigens and the Vg9Vd2 TCR have yet to be characterized, MookerjeeBasu and colleagues suggested that cell surface-bound F1.ATPase can act as a phosphoantigen-presenting molecule (10). F1.ATPase-coated beads stably bound to an adenylated derivative of IPP, and promoted TCR aggregation, cytokine secretion, and cytotoxic activity (10).…”
Section: T-cell Receptor Agonists For Activation Of Vg9vd2 T Cellsmentioning
confidence: 99%
“…Alternatively, CD277 might promote recruitment of other receptors recognized by the V␥9V␦2 TCR, such as ecto-F1-ATPase, which is a known ligand for V␥9V␦2 TCR. 44,45 The restricted but mandatory implication of CD277 in the activation of particular human ␥␦ T-cell subsets brings to mind the mandatory role played by Skint-1, another member of the extended B7 receptor family, in the selection of murine intraepidermal ␥␦ T cells. [16][17][18] Although Skint-1 deficiency prevents differentiation of T cells expressing invariant V␥5V␦1 TCR, it has no effect on other ␥␦ or ␣␤ T-cell compartments.…”
Section: Discussionmentioning
confidence: 99%
“…In an attempt to reconcile the established reactivity of Vc9Vd2 T cells to non-peptidic pAgs and these new observations of alternative stress-induced ligands, experiments were carried out to demonstrate that ATP synthase can also potentially bind to pAgs, and it was concluded that it seemingly has the appropriate features to function as a possible pAg presenting molecule for Vc9Vd2 T cells. 76 More recently, another putative Vc9Vd2 T cell tumor antigen, human MutS homologue 2 (MSH2), was identified using a peptide-based affinity screening system for the CDR3 of the d chain. 77 MSH2 is normally located in the nucleus where it functions as a DNA mismatch repair gene, but it is often mutated in a number of different types of epithelial cancers and can be ectopically expressed.…”
Section: Vd2 T Cells: To Know the Complex Burden Of Being Humanmentioning
confidence: 99%